prosedur pemeriksaan CT Cardiac dengan Kasus Coronary Artery By Pass Grafting (CABG) di Instalasi Radiologi MRCCC SILOAM Hospital Semanggi - Atika Dian Utami; Yeti Kartikasari; Sigit Wijokongko (Poltekkes Kemenkes Semarang, 2017)
Background : Coronary Artery By Pass Grafting (CABG) is one of the intervention treatments of Coronary Heart Disease (CHD), by creating a new channel through the coronary artery which is narrowed or blocked. The purpose of this research is to know the procedure of Cardiac CT examination with CABG case, acceptable Heart Rate range and how to lower Heart Rate range and how to lower Heart Rate at Radiologt Installation of MRCCC Siloam Hospital Semanggi.Methods : This type of research is qualitative with case study approach. The data were collected from April - June 2017 at Radiology Installation of MRCCC Siloam Hospital Semanggi by observation method, interview with 3 radiographers, 2 radiology specialists and 1 sending doctor and documentation. Data obtained from the study were analyzed by interactive model, with data reduction stage, data presentation and conclusion.Result : The results of this study stated that the procedure of Cardiac CT examination with CABG scan start from subclavia to the diaphragm to show the graft, the amount of contrast media used 20 cc more and the amount of saline used 10 cc more, Beta Blocker and Vasilidator not given because CT Scan with 256 slices work quickly so as to suppress the movement of the heart with optimal. Acceptable Heart Rate range is 65 - 80 bpm. How to lower high Heart Rate by giving patients education one day before the examination, which is does not consume drugs which can increase Heart Rate and do not perform heavy activities. Patients with unstable Heart Rate should be given Beta Blocker 2-3 days before the examinationConlusion : Based on the results of the study, the range of CT Cardiac examination with CABG cases differs from the usual cardiac CT range and using MSCT 256 radiology specialists slice does not need to consider the patient's heart rate